PRECISION TEST OF QED BY DIRECT COMPARISON OF E+E--]GAMMA-GAMMA AND E+E-]E+E-AT 29 GEV - Derrick, M; Gan, K; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; Wood, D; Blockus, D; Brabson, B; et al. (1986)
The ratio of differential cross sections for the reactions e+e- → γγ and e+e- → e+e- is measured at s = 29 GeV in the central polar angle region, |cos θ| < 0.55, and compared to the same ratio calculated by QED to order α3. The ratio of these ratios, integrated over this angular region, is 1.007±0.009±0.008, demonstrating excellent agreement between theory and experiment. The 95% confidence limits on the QED cut-off parameters for the γγ final state are Λ+ > 59 GeV and Λ- > 59 GeV. © 1986.